Fourier transform infrared spectroscopy (FTIR) for identification of sugar adulterants in mulberry molasses (pekmez) - Cebi, N.; Tikiloglu, F. O.; Durak, M. Z.; Cengiz, M. Fatih (PLAPIQUI(UNS-CONICET), 2024)
Fourier Transform Infrared Spectroscopy (FTIR) and chemometrics were successfully used in this research in conjunction with the Attenuated Total Reflectance (ATR) technique to determine mulberry molasses (MM) cane sugar adulteration. Mulberry molasses was adulterated by incorporating two fructose syrups (FS), one glucose syrup (GS), one sucrose syrup (SS), and two specific high fructose corn syrups (HFCS). Calibration sets were developed for mulberry molasses by spiking sugar syrups. The actual percentage of adulteration linked to FTIR predicted results by regression analysis. The preferred spectral range was 1184-944 cm-1 - 1 for prediction of adulteration levels of F20, F30, HFCS50, HFCS55 and 1090-950 cm-1 - 1 for sucrose. This method was employed to distinguish between mulberry molasses and adulterated samples. According to the findings, the FTIR technique is an accurate and affordable method that can rapidly detect sugar adulteration in mulberry molasses.
Keywords: FTIR; Sugar adulterants; Mulberry molasses; Chemometrics; RAPID-DETERMINATION; HONEY ADULTERATION; SYRUPS; Engineering